Study on the Deformation Behavior and Mechanical Properties of Lightweight Economic Stainless Steels with Varying Al and Mn Contents - Nuoteng Xu; Guanghui Chen; Qi Zhang; Haijiang Hu; Guang Xu (Journal of Manufacturing and Materials Processing)
In order to reduce the density and alloy cost of austenitic stainless steel, this study designed Fe-0.35C-12Cr-5Ni-(0,2,4)Al-(6,10)Mn (wt.%) stainless steels with different Al and Mn contents. The effects of Al and Mn contents on the microstructure, deformation behavior, and mechanical properties were investigated using microstructural analyses, quasi-static tensile tests, and Charpy impact tests. The results showed that an increase in Al content led to the formation of austeniteferrite duplex microstructure, while an increase in Mn content reduced the ferrite fraction. In the Al-free steel, the deformation mechanism was deformation-induced α′-martensitic transformation. When the Al content increased to 2 wt.%, the deformation mechanism was primarily mechanical twinning due to the increased stacking fault energy caused by Al. This resulted in a lower tensile strength but better toughness. When the Al content was further increased to 4 wt.%, the proportion of mechanical twinning decreased. The presence of ferrite led to cleavage at the fracture surface. The cleavage fracture explained the low elongation and toughness of duplex stainless steels. However, the elongation and toughness were enhanced with the increase in Mn content.